2015
DOI: 10.1186/s12864-015-1950-1
|View full text |Cite
|
Sign up to set email alerts
|

Diverse regulatory factors associate with flowering time and yield responses in winter-type Brassica napus

Abstract: BackgroundFlowering time, plant height and seed yield are strongly influenced by climatic and day-length adaptation in crop plants. To investigate these traits under highly diverse field conditions in the important oilseed crop Brassica napus, we performed a genome-wide association study using data from diverse agroecological environments spanning three continents.MethodsA total of 158 European winter-type B.napus inbred lines were genotyped with 21,623 unique, single-locus single-nucleotide polymorphism (SNP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 59 publications
(67 reference statements)
9
67
0
1
Order By: Relevance
“…Our results showed that grouping for both spring and winter types based on FT paralogs was not that distinct (Fig. 10) suggesting that other key flowering genes such as FLC and FRI may have contributed to diversification of these morphotypes (Schiessl et al , 2017; Schiessl et al , 2015).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Our results showed that grouping for both spring and winter types based on FT paralogs was not that distinct (Fig. 10) suggesting that other key flowering genes such as FLC and FRI may have contributed to diversification of these morphotypes (Schiessl et al , 2017; Schiessl et al , 2015).…”
Section: Resultsmentioning
confidence: 84%
“…In addition, flowering is also affected by other external factors such as ambient temperature, insect-pests, pathogens, light quality, and abiotic stress, and some of these integrate with the flowering pathways. Genetic analyses based on classical linkage mapping (quantitative trait loci: QTL) and genome-wide association studies (GWAS) have revealed that flowering time in canola is a multi-genic trait (Ferreira et al , 1995; Long et al , 2007; Nelson et al , 2014; Raman et al , 2016b; Raman et al , 2013; Raman et al , 2016c; Schiessl et al , 2015; Xu et al , 2016; Yi et al , 2018). Candidate genes underlying flowering time variation due to vernalisation have been identified in B. napus (Fletcher et al , 2015; Hou et al , 2012; Raman et al , 2016b; Raman et al , 2013; Tadege et al , 2001; Wang et al , 2011; Zou et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, mutations in genes involved in the flowering time control can affect seed yield components [65]. The selection of the genes involved in the flowering time regulation may play a potential role in the adaptation of rapeseed to highly divergent environments [66]. Future cultivar selection should also consider the crop phenology and influence of the environment [67].…”
Section: Time Of Sowing N Rates and Growing Seasonsmentioning
confidence: 99%
“…Dalton-Morgan et al 2014). These arrays comprise an extremely valuable resource for the genetics and breeding communities in Brassica, and have already been used for applications such as linkage mapping of agricultural traits for flowering time, plant height, seed yield, germination, seedling emergence and disease resistance Schiessl et al 2015), tracking allele inheritance in interspecific hybrid populations (Mason et al 2014a(Mason et al ,b, 2015a and species identification in germplasm collections (Mason et al 2015b). SNP arrays are fast, highly reproducible and produce easy-to-analyse data (Hayward et al 2012).…”
Section: Proximity To Model Plant a Thalianamentioning
confidence: 99%